The impact of Brexit on the VAT regulation for B2B transactions of goods between EU and UK : on the post Brexit, do the new VAT rules violate the VAT principles and leads agents to perform VAT avoidance? - Sousa, Ana Rita Fontes (2023)
This thesis focuses on study of how Brexit impacted the VAT regulation of the trade of goods between EU and UK, after 1st January 2021. The main objective is to conclude what are the new VAT rules applicable for the transaction of goods between EU and UK, how it impacts the consumption behaviour of EU and UK agents, if the new laws created violate the VAT principles and if there are ways where agents could, lawfully, perform VAT avoidance when importing from EU/ UK to UK/EU. In general terms, I was able to conclude with this thesis that only one of the three goals of the Brexit Trilemma was achieved, however it was done by violating the neutrality principle of VAT. Additionally, I was also able to conclude that the Protocol created a way of passing the goods from EU to GB through NI without paying VAT at any stage. The available literature on the subject was very hard to find since firstly, considering that this is a very recent subject, the VAT agents and VAT specialist still have a lot of doubts on what the rules are applied in each case (which indeed, leads to them not to write a lot about it) and secondly, this implies reading many laws in order to understand how VAT works in each transaction between EU, GB and NI. In this regard, my thesis was done mostly by reading what is stated on HMRC website regarding this topic, by reading the VATA 1994 on the sections related with Brexit and by reading the VAT Directive. Additionally, I was also able to find a very complete book “The Law and Practice of the Ireland-Northern Ireland Protocol” and a thesis made on this topic by an Italian student “A Tax Perspective on Brexit: which consequences on VAT and Customs Procedures?”, which help me to confirm if my understanding of the law was correct. The investigation ended on 16th February 2023, meaning that any laws created after that date where not consider on this thesis.